NARMAX approach for micro positioning stage piezoelectric actuator hysteresis identification - Ounissi Amor; Azeddine Kaddouri; Rachid Abdessemed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The structure of the model may either be inferred via an experimental study or just by looking at the input and output data. A novel nonlinear autoregressive with exogenous inputs (NARMAX) method for identifying PEA piezoelectric positioning mechanisms is put forward in this study. The developed model enables accurate prediction of the hysteresis of the PEAs. The accuracy of the model built from the input and output data will be assessed by comparison with a LuGre model. The results of the identification show that the recommended approach is successful and that it has a high degree of identification precision within an absolute error range of one micron. The findings demonstrated the potential of the suggested method for classifying nonlinear PEAs.